The Dramatic Effect of Water Structure on Hydration Forces and the Electrical Double Layer - Hedley, Jonathan G.; Berthoumieux, Hélène; Kornyshev, Alexei A. (Journal of physical chemistry. C, 2023)
Forces between hydrophilic surfaces mediated by water are important in various systems from lipid membranes and solid surfaces to colloids and macromolecules, first discovered as a significant addition to DLVO forces at the nanoscale. These “hydration forces” have been studied in great detail experimentally using osmotic stress measurements, surface force apparatus, and AFM, and they have also been the subject of multiple theories and simulations. One spectacular feature observed in experimental and simulation studies was the nonmonotonic, oscillatory decay in the forces between atomically smooth surfaces. Forces between “rougher” surfaces exhibit only quasi-exponential, monotonic decay. Here we revisit this hydration force problem by exploring the consequences of an extended phenomenological Landau–Ginzburg approach that describes nonlocal correlations in water, linking them with the key features of the wave-number k-dependent nonlocal dielectric function of water. With corresponding boundary conditions, this theory predicts the observed oscillatory decay in hydration force between ideally flat surfaces, the oscillatory mode disappearing with just a tiny roughness of the surfaces (of mean height ca. of the size of a water molecule). This study also brings an important side message. Explanation of these observations appears only possible under an assumption of two modes of polarization in water, consistent with the behavior of the response function, i.e., Lorentzian at small k and resonance-like at higher k. This resolves the “force oscillation–non-oscillation” paradigm, which is a strong, although indirect indication of the existence of these two modes. We also consider other important subjects, such as how the distribution of ions near a charged surface reacts to the propensity for overscreening oscillations due to polarized water. This is important not only for the interactions between charged surfaces but also for the fundamental understanding of the structure of the electrical double layer at electrochemical interfaces. We show that even in dilute electrolytes, the distribution of ions in the vicinity of the polarized interface follows, although not literally, preferential positions corresponding to the potential wells caused by “resonance” water layering. For a sharp interface, the theory predicts that the decaying spatial oscillation profiles extend over a 1 to 2 nm distance from the interface. With the smearing of the interface and the corresponding suppression of the resonance water layering, oscillations in the spatial distribution of ions subside, resulting in a familiar Gouy–Chapman–Stern picture. At longer distances from the interface, whether smeared or not, the ion distribution profiles become Gouy–Chapman-like. The effect of the boundary conditions on water polarization at the interface goes beyond a trivial shift of the potential of zero charge. We show that they can dramatically affect the ion distribution near the charged surface. Last, but not least, we study how the interfacial water layering influences the double layer capacitance and show the effect of the boundary conditions on the slopes of Parsons–Zobel plots, resolving some recently discussed puzzles.